KEMAMPUAN MENENTUKAN GAGASAN UTAMA SEBUAH WACANA PADA SISWA KELAS VII SMPN 12 BANDAR LAMPUNG - Herlili, Emi (STKIP PGRI Bandar Lampung, 2018)
The problem raised in this research relates to the level of students' ability in determining the main idea of ​​a discourse. Students are still not fully able to discover, express and explain the main ideas contained in the discourse. Students still tend not to understand the characteristics of a discourse. The purpose of research to determine the ability to determine the main idea of ​​a discourse of VII class students even semester SMP Negeri 12 Bandar Lampung. To achieve the goal, used descriptive research method. The population of this study is all students of class VII even semester SMP Negeri 12 Bandar Lampung, which amounted to 272 students. Sample of this research as much as 11% of population amount, this research sample as many as 11% * 272 = 30 students. The research instrument used to obtain data is in the form of a written test by way of assigning students to find the main idea in a discourse. Based on the data analysis and discussion in this study obtained the conclusion that the ability to determine the main idea for the whole aspect or indicator pertained enough with the percentage 63.26%.